Enhancing the deaf children's spoken language by using storytelling - Fifi Elvia; Tri Rukmana; Nadha Mustika; Viny Anggradini Puspitaloka (Atfaluna: Journal of Islamic Early Childhood Education, 2022)
This study aims to describe the storytelling method as an alternative to enhancing the spoken language of deaf children. The method used in this research is a qualitative method with a descriptive approach. The technique of collecting the data was technique and observation. The student's principal, teachers, and parents become the informants. The researchers analyzed the data using a single case by determining the subject to be studied, then using research data sources, collecting and analyzing them, reducing and concluding and compiling. The results showed that the use of the storytelling method was effective in enhancing spoken language in deaf children. It is hoped that the school will routinely hold activities that can enhance spoken language in deaf children, using both the storytelling method and other methods